Application and development of CRISPR technology in the secondary metabolic pathway of the active ingredients of phytopharmaceuticals - Gao, Haixin; Pei, Xinyi; Song, Xianshui; Wang, Shiying; Yang, Zisong; Zhu, Jianjun; Lin, Qiupeng; Zhu, Qinlong; Yang, Xiangna (Frontiers in Plant Science, 2025)
As an efficient gene editing tool, the CRISPR/Cas9 system has been widely employed to investigate and regulate the biosynthetic pathways of active ingredients in medicinal plants. CRISPR technology holds significant potential for enhancing both the yield and quality of active ingredients in medicinal plants. By precisely regulating the expression of key enzymes and transcription factors, CRISPR technology not only deepens our understanding of secondary metabolic pathways in medicinal plants but also opens new avenues for drug development and the modernization of traditional Chinese medicine. This article introduces the principles of CRISPR technology and its efficacy in gene editing, followed by a detailed discussion of its applications in the secondary metabolism of medicinal plants. This includes an examination of the composition of active ingredients and the implementation of CRISPR strategies within metabolic pathways, as well as the influence of Cas9 protein variants and advanced CRISPR systems in the field. In addition, this article examines the long-term impact of CRISPR technology on the progress of medicinal plant research and development. It also raises existing issues in research, including off-target effects, complexity of genome structure, low transformation efficiency, and insufficient understanding of metabolic pathways. At the same time, this article puts forward some insights in order to provide new ideas for the subsequent application of CRISPR in medicinal plants. In summary, CRISPR technology presents broad application prospects in the study of secondary metabolism in medicinal plants and is poised to facilitate further advancements in biomedicine and agricultural science. As technological advancements continue and challenges are progressively addressed, CRISPR technology is expected to play an increasingly vital role in the research of active ingredients in medicinal plants.